2001
DOI: 10.1046/j.1469-7580.2001.19940407.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the arterial pattern in the upper limb of staged human embryos: normal development and anatomic variations

Abstract: A total of 112 human embryos (224 upper limbs) between stages 12 and 23 of development were examined. It was observed that formation of the arterial system in the upper limb takes place as a dual process. An initial capillary plexus appears from the dorsal aorta during stage 12 and develops at the same rate as the limb. At stage 13, the capillary plexus begins a maturation process involving the enlargement and differentiation of selected parts. This remodelling process starts in the aorta and continues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
174
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(186 citation statements)
references
References 22 publications
6
174
2
4
Order By: Relevance
“…Another study has reported an anastomosis joining the brachial and brachioradial artery at the elbow in 3 of the 21 cases (14±3%) which is a higher incidence when compared to the present study [20].…”
Section: Anastomotic Arterycontrasting
confidence: 47%
“…Another study has reported an anastomosis joining the brachial and brachioradial artery at the elbow in 3 of the 21 cases (14±3%) which is a higher incidence when compared to the present study [20].…”
Section: Anastomotic Arterycontrasting
confidence: 47%
“…Adachi [1] and Libersa et al [4] mention the 2DMA as source of PPDA; Edwards [15] relates this origin could be possible due existing anastomoses at the second web space, but in his series of specimens, he did not find it. Coleman and Anson [2] described its presence limited to the first and second digital web spaces.…”
Section: Discussionmentioning
confidence: 97%
“…Variations in the branching patterns of the major arterial trunks have been reported with an incidence of over 20% in human adult limbs 7 . Despite this, several variations in its origin and in the course of the DBA, like other vessels of the upper limb, could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…From this axial artery, which represents the axillary, brachial, and anterior interosseous, the forearm arteries appear successively. The axillary and brachial arteries begin their development at stages 16 and 17 successively and, therefore, anatomical variations including these vessels may have originated at this time 6,7 . In 55% of the cases 1,2 , the deep brachial artery (DBA) is the larger branch issued from the brachial artery (BA), and it leaves near the bottom edge of the teres major muscle to penetrate above the medial intermuscular septum on the lower triangular axillary space together with a radial nerve (RN) 8,9 .…”
Section: Introductionmentioning
confidence: 99%